Prediction of massive transfusion in trauma patients in the surgical intensive care units (THAI-SICU study) - Osaree Akaraborworn (2019)
© 2019 Chinese Medical Association Purpose: After damage control surgery, trauma patients are transferred to intensive care units to restore the physiology. During this period, massive transfusion might be required for ongoing bleeding and coagulopathy. This research aimed to identify predictors of massive blood transfusion in the surgical intensive care units (SICUs). Methods: This is an analysis of the THAI-SICU study which was a prospective cohort that was done in the 9-university-based SICUs in Thailand. The study included only patients admitted due to trauma mechanisms. Massive transfusion was defined as received ≥10 units of packed red blood cells on the first day of admission. Patient characteristics and physiologic data were analyzed to identify the potential factors. A multivariable regression was then performed to identify the significant model. Results: Three hundred and seventy patients were enrolled. Sixteen patients (5%) received massive transfusion in the SICUs. The factors that significantly predicted massive transfusion were an initial sequential organ failure assessment (SOFA) ≥9 (risk difference (RD) 0.13, 95% confidence interval (CI): 0.03–0.22, p = 0.01); intra-operative blood loss ≥ 4900 mL (RD 0.33, 95% CI: 0.04–0.62, p = 0.02) and intra-operative blood transfusion ≥ 10 units (RD 0.45, 95% CI: 0.06 to 0.84, p = 0.02). The probability to have massive transfusion was 0.976 in patients who had these 3 factors. Conclusion: Massive blood transfusion in the SICUs occurred in 5%. An initial SOFA ≥9, intra-operative blood loss ≥4900 mL, and intra-operative blood transfusion ≥10 units were the significant factors to predict massive transfusion in the SICUs.